2014
DOI: 10.1007/s10120-014-0361-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of infectious complications on gastric cancer recurrence

Abstract: Background Postoperative infectious complications increase disease recurrence in colorectal cancer patients. We herein investigated the impact of infectious complications on gastric cancer recurrence after curative surgery. Methods In total, 502 patients who underwent R0 resection for gastric cancer were reviewed. Patients were classified into those with infectious complications (IC group) and those without infectious complications (NO group). The risk factors for recurrence-free survival (RFS) were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 14 publications
6
80
0
1
Order By: Relevance
“…have analyzed the impact of postoperative complications on recurrence and survival after gastric cancer resection. In this study conducted in Spain, the incidence of postoperative complications (Clavien‐Dindo grade II or higher) was reported as 59.8%, which is somewhat higher than that reported elsewhere 36, 37, 38. They have concluded that these complications do not have a negative impact on oncological outcome.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…have analyzed the impact of postoperative complications on recurrence and survival after gastric cancer resection. In this study conducted in Spain, the incidence of postoperative complications (Clavien‐Dindo grade II or higher) was reported as 59.8%, which is somewhat higher than that reported elsewhere 36, 37, 38. They have concluded that these complications do not have a negative impact on oncological outcome.…”
Section: Resultsmentioning
confidence: 59%
“…Several studies have reported a negative impact of postoperative complications on patient prognosis after gastric cancer surgery using multivariate analysis 35, 36, 37, 38, 39. Table 2 and Figure 2 show the summarized results of studies evaluating the prognostic impact of postoperative complications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous paper [23], we reported the association between intraabdominal infectious complications after surgery for gastric cancer and survival outcomes. Hayashi et al [24] and Kubota et al [25] also reported that complications following surgery for gastric cancer shorten relapse-free and overall survival rates. In the present study, survival outcomes may have been affected by the increased complications resulting from the concurrent performance of gastrectomy and hepatectomy.…”
Section: Discussionmentioning
confidence: 99%